Ethylene and changes during ripening in 'Horvin' plum (Prunus domestica L.) fruits (2015)
The plum is a fruit prized for its nutraceutical properties because of its high content of fiber and sorbitol, which aid in digestion; furthermore, it is characterized as containing antioxidant pigments and an antiseptic action with anthocyanins. These fruits are classified as climacteric and continue the process of respiration and ripening after harvesting; because of this, it is necessary to harvest early so they can withstand transport, which often causes the fruits to not reach the consumption maturity required by consumers. The effect of ethylene on the ripening of plum fruits was evaluated, for which a completely randomized design with 10 treatments was used, which resulted from the combination of two factors plus a control without applications. The first factor was the ethylene dose (100; 1,000 and 2,000 mg L-1) and the second factor was the length of exposure to the ethylene (5, 10 and 15 minutes). The fruits were stored at room temperature for 9 days. In the fruits treated with ethylene, a significant increase in the respiration index and total soluble solids was observed. Additionally, greater total titratable acids and firmness values were obtained with the control treatment than with the ethylene; similarly, the ethylene application increased the fresh mass loss in the plum fruits. Overall, differences between the fruits treated with ethylene and the control were observed, but not between the doses, indicating that the lowest ethylene dose (100 mg L-1) can obtain the desired uniformity in plum fruits.